Design and Construction of Employee Recruitment System Application using Profile Matching Method - Mahendra, M. Azmi; Firmansyah, Maulana; Triyono, Gandung (P3M Politeknik Negeri Bengkalis, 2025)
The employee recruitment process is one of the important aspects of human resource management, which ensures a match between company needs and available candidates. This research aims to design an E-Recruitment system based on Profile Matching to improve efficiency and accuracy in the employee selection process at PT XYZ. The research methods used include literature study, observation, and interviews with the HRD team. System development follows the SDLC waterfall model, which includes planning, analysis, design, implementation, and testing stages. In this case study, we use data samples from 5 applicants. For the criteria used, there are 3 criteria, namely administration, interview results, and skills/expertise. The results showed that the developed system was able to automate the selection process, reduce administrative burden, and increase objectivity in candidate selection. In conclusion, the implementation of Profile Matching-based E-Recruitment can optimise the recruitment process, but still needs to be combined with other selection methods to get a more comprehensive picture of candidates.